2022
DOI: 10.3390/jcm11030657
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Complications of Patients with SARS-CoV-2 Infection in Neurosurgery

Abstract: Background: The outbreak of coronavirus disease 2019 (COVID-19) has been rapidly evolving, resulting in a pandemic, with 270,031,622 infections according to the World Health Organization. Patients suffering from COVID-19 have also been described to suffer from neurologic and coagulopathic symptoms apart from the better-known flu-like symptoms. Some studies showed that patients suffering from COVID-19 were likely to developed intracranial hemorrhages. To our knowledge, only a few studies have investigated posto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…4,19,20 Several studies examining postoperative complications in patients with COVID-19 found increased rates of thromboembolism when compared with patients without COVID-19. 6,7,21 In a study by Deng et al 8 that examined postoperative outcomes by time from COVID-19 infection to the surgical procedure found an increased risk of pulmonary embolism in patients undergoing surgery 0 to 4 weeks after COVID-19 diagnosis, but no difference at 4 to 8 weeks or > 8 weeks, and no difference in deep vein thrombosis at any time point. This study found an increased risk of thromboembolic events in all subspecialties analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…4,19,20 Several studies examining postoperative complications in patients with COVID-19 found increased rates of thromboembolism when compared with patients without COVID-19. 6,7,21 In a study by Deng et al 8 that examined postoperative outcomes by time from COVID-19 infection to the surgical procedure found an increased risk of pulmonary embolism in patients undergoing surgery 0 to 4 weeks after COVID-19 diagnosis, but no difference at 4 to 8 weeks or > 8 weeks, and no difference in deep vein thrombosis at any time point. This study found an increased risk of thromboembolic events in all subspecialties analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by the COVIDSurg Collaborative reported that routine preoperative testing for SARS CoV2 is associated with lower postoperative pulmonary complications in major surgeries ( 22 ).. In addition, Greuter et al reported a higher rate of postoperative thrombotic complications in patients undergoing neurosurgical procedures ( 8 ). This is explained by the state of hypercoagulation with increased rate of heparin-binding proteins, which led to an increased rate of thrombotic complications.…”
Section: Discussionmentioning
confidence: 99%
“…While Chacon-Quesada et al reported a significant reduction of surgical site infections in their neurosurgical department due to the implemented measures; Abduljawwaad et al did not note any relevant changes in patient characteristics, duration of hospital stay and mortality rates in a nationwide network of spine care centers ( 6 , 7 ). An increased rate of complications in patients undergoing neurosurgery with concomitant SARS-CoV-2 infection has been by described by a group in Switzerland ( 8 ).…”
Section: Introductionmentioning
confidence: 99%